(untitled) (Linguostylistic Studies, 2021)
The article elucidates specific features of the biographical and ideological image of the famous Ukrainian linguist and politician Sviatoslav Karavanskyi (1920–2015). The study seeks to identify the integrity of the nationalist worldview of the linguist that developed in the conditions of more than30 years of restraint by the Moscow totalitarian regime and 37 years of emigration. The analysis has been conducted in terms of two principal conceptions of the thinker, scientist, and fighter: historical and socio-lingual. Under the current socio-political conditions, the topicality and appropriateness of the socio-lingual methodology of the linguist and politician are coherent. Ukrainian lingual and historical truth is interpreted by the linguist and politician against the background of the American-European strategies concerning the aggressor-country Moscow and the newly-established independent state of Ukraine. According to S. Karavanskyi, the issue of the official status of the Ukrainian language is identical to the Ukrainian statehood existence and, vice versa, any preferences given to the Russian language imply a return of Ukraine to the colonial status. That is, Ukrainian and Russian languages in Ukraine are two political poles: independence and colonialism, statehood and statelessness. In the focus of his judgments are activities of prominent and equally distinguished figures of our history – T. Shevchenko, S. Bandera, and R. Shukhevych. They are considered as a litmus test for the national maturity of the Ukrainians themselves and an approach to explain the European structures’ irritation caused by a fear of a new competitor in the heart of Europe. The linguist’s main criterion of perceiving the global and the national is the cross-cutting concept of truth substantiated in his publicist works and regarded by him as a unique thing we have and fight with. In this man, heroic history of almost a century is woven with a pervasive Ukrainian nation ideal – to be in its otherness.